ANALISIS ORIENTASI KEWIRAUSAHAAN DAN KEUNGGULAN BERSAING DALAM MENINGKATKAN KINERJA PEMASARAN UMKM DI KOTA KENDARI - Laode Asfahyadin Aliddin; Sudirman Zaid; Samdin; Nursaban Rommy; Dzulfikri Azis Muthalib (Jurnal Manajemen dan Kewirausahaan, 2025)
Abstract The purpose of this study is to examine and explain entrepreneurial orientation and competitive advantage in improving the marketing performance of MSMEs in Kendari City. This study design is based on a quantitative approach using cross-sectional survey data collection methods. Data collection was conducted using a questionnaire instrument. The research sample consists of 96 MSME actors in Kendari City. The analytical tool used for hypothesis testing is multiple regression analysis. The study results indicate that: (1) Entrepreneurial orientation has a positive and significant effect on marketing performance. This means that an increase in the entrepreneurial orientation of MSME actors in Kendari City will be followed by a tangible improvement in marketing performance. (2) Competitive advantage has a positive and significant effect on marketing performance. This means that an increase in the competitive advantage of MSME actors in Kendari City will be followed by a tangible improvement in marketing performance.